A large-scale observational study linking various kinds of physical exercise to lipoprotein-lipid profile. Issue 1 (10th May 2021) - Lin, Wan-Yu
Abstract: Background: Being a major cardiovascular risk factor, dyslipidemia is a critical problem in public health. Recommendations in performing regular physical exercise are important to prevent dyslipidemia. Methods: Based on a discovery cohort with 27, 735 subjects and a replication cohort with 67, 512 subjects, we evaluated the associations of regularly performing 23 exercises with 4 dyslipidemia indices measured from serum, including triglyceride (TG), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), and TG/HDL-C ratio. Regular exercise was defined as performing 30 min of "exercise" three times a week. "Exercise" includes leisure-time activities such as jogging, swimming, etc. Sex, age, body mass index, alcohol drinking, cigarette smoking, and education level were adjusted in all statistical analyses. Results: Among the 23 exercises, only jogging was associated with a decreased level of TG (95% confidence interval [C.I.] = 5.9–14.5 mg/dL) and TG/HDL-C ratio (95% C.I. = 0.22–0.49). A total of 5 exercises were associated with an increased level of HDL-C, including jogging (95% C.I. = 2.1–3.3 mg/dL), swimming (95% C.I. = 1.6–3.3 mg/dL), dance dance revolution (95% C.I. = 1.5–3.4 mg/dL), international standard dancing (95% C.I. = 1.0–2.7 mg/dL), and cycling (95% C.I. = 0.6–1.8 mg/dL). These significant findings were further well replicated in the cohort of 67, 512 subjects. Conclusion: Regular jogging was not only associated with an increased level of HDL-C, but also the only one exercise associated with a decreased level of TG and TG/HDL-C ratio. Nonetheless, jogging may be difficult to engage in for subjects with limited exercise capacity. We here found that swimming, dancing, and cycling are also significantly associated with an increased level of HDL-C. People who are seeking exercise to improve their lipoprotein-lipid profiles can have other choices now.